Efficacy of bacterial fermented oilcake mix as fishmeal substitute in the diet of tiger shrimp, Penaeus monodon (Fabricius) post larvae - Joseph, Imelda; Paulraj, R (Indian Journal of Fisheries, 2011)
Diets incorporated with varying levels (5, 15, 25 and 35%) of bacterial fermented oil cake mix, derived by solid-state fermentation (SSF) as fishmeal replacement, were evaluated in Penaeus monodon post larvae for growth, digestibility and body composition through a 42 days laboratory experiment. A diet containing 35% fishmeal and no fermented ingredient mix was used as the control. Pure culture of Bacillus coagulans MTCC-2449 was used for SSF and the 36 h fermented product was incorporated in the diets. Analysis of response data revealed that the shrimp fed diet containing 35% fermented ingredient mix (100% fishmeal substitution) had significantly higher (P<0.05) mean weight gain (0.63Â±0.03 g), better feed conversion ratio (1.58), apparent protein utilization (25.65) and protein efficiency ratio (1.71) than all other diets as well as the control. The apparent protein digestibility (86.56%) and apparent fat digestibility (94.55%) were also found to be the highest for this diet. The survival rate was 100% in all the treatments and the control.